Temperature‐Responsive 4D Liquid Crystal Microactuators Fabricated by Direct Laser Writing by Two‐Photon Polymerization. Issue 2 (19th November 2021) - del Pozo, Marc; Delaney, Colm; Pilz da Cunha, Marina; Debije, Michael G.; Florea, Larisa; Schenning, Albert P. H. J.
Abstract : Over the past decade, progress in direct laser writing by two‐photon polymerization (DLW‐TPP) of stimuli‐responsive materials has made considerable inroads into the realization of microactuators. With the focus on performing complex tasks such as walking, grasping, or delivering drugs, these actuators require a controlled preprogrammed actuation. Liquid crystalline microactuators enable such programmed movement when the mesogenic alignment can be successfully controlled. To date, this has necessitated low crosslink density networks, which are not readily conducive to the fabrication of 3D geometries. Herein, a liquid crystalline photoresist is reported, which results in a highly crosslinked network, that permits fabrication of 4D microactuators having a highly crosslinked network in which the molecular alignment is determined by the alignment layers in the cell construct. In addition to controllable deformation of the microactuators, they also display a characteristic and unique polarization color that can be used for both identification and reporting in real time, enabling their integration into sensing and anti‐anticounterfeiting microdevices. Abstract : Untethered microactuators hold enormous potential for applications in fields spanning medicine to microfluidics. Their miniaturization still remains a challenge, specially when specific geometries displaying preprogrammed deformations are desired. Here, a liquid crystalline photoresist with a high fraction of crosslinkers is reported and the structural and optical responses of several temperature responsive 3D constructs are studied.